MAKNA LABEL HALAL INDONESIA DALAM PERSPEKTIF SEMIOTIKA: ANALISIS SEMIOTIKA ROLAND BARTHES - Faisal Muzzammil (Balai Diklat Keagamaan Jakarta, 2023)
The Ministry of Religion of the Republic of Indonesia, through its official website and Instagram account in March 2022, established and released the